Effectiveness of residential buildings renovation on the example of Kaunas City - Kveselis, Vaclovas; Dzenajavičienė, Eugenija Farida; Lisauskas, Aurimas (International Conference “Environmental Engineering”, 2017)
Improvement of energy efficiency in buildings is one of the main strategic goals of country’s energy strategy and its’ implementation policy. This goal is being implemented using support measures and implementation instruments in public and residential buildings. Implementation programs were designed and are being implemented in this sector since year 2004; however, there is still lack of research investigating the effectiveness of implemented actions in terms of environmental, economic, and social sustainability using respective criteria. On the other hand, there is lack of objective information for wider research based on measured data, as most of the data comes from programs administrators as estimated energy consumption and savings. The paper provides main criteria for defining renovation sustainability of multi-apartment residential buildings as well as initial assessment of energy efficiency improvement in such buildings implemented under programs partly funded by EU funds and Modernization program for multi-apartment houses. The Kaunas district heating company provided data of metering readings for 103 buildings which are fully or partially renovated in Kaunas City and Kaunas Regional municipalities and covers period of 12 years. The results of investigation show wide scattering of renovation effectiveness regarding renovation costs, energy savings and costs of saved energy.